Chemical Structure Change of Magnesium Oxide in the Wet Oxidation Delignification Process of Biomass with Solid Alkali. Issue 13 (22nd May 2017) - Jiang, Yetao; Ding, Ning; Luo, Bin; Li, Zheng; Tang, Xing; Zeng, Xianhai; Sun, Yong; Liu, Shijie; Lei, Tingzhou; Lin, Lu
Abstract: We have developed a facile MgO‐based wet oxidation process for biomass pretreatment. Herein, we performed kilo‐scale experiments to elucidate the transformations of Mg in the process as well as the recycling of the MgO‐based solid alkali. A new intermediate, magnesium oxide carbonate [Mg3 O(CO3 )2 ] generated in situ during the process was shown for the first time, which could provide an indispensably weak but adequate alkaline environment to support the oxygen delignification reaction. However, once the solid alkali was transformed into hydromagnesite [Mg5 (CO3 )4 (OH)2 ] with sufficient CO2, the hydromagnesite form would prevent the solid alkali from developing resistance to the acidic gaseous CO2 . Ultimately, if we take the features of the solid alkali into consideration, alkali recovery for this process was fulfilled easily without concentration or causticization, which are of high cost but unavoidable in the traditional recycling of sodium alkali. Abstract : Recover like no other : A facile alkali recovery procedure for the MgO‐based wet oxidation process is described. After biomass is pretreated by MgO‐based WO, approximately 20 and 15 wt. % of MgO in the form of Mg‐rich solid particles is recovered directly from the solid fractions. The residual Mg could be precipitated easily by metathesis to give a total MgO recovery of 94.6 wt. %.